Long-term Results of the Patients with Regional Transient Osteoporosis - Kenan Akgün (Galenos Yayinevi, 2002)
Transient regional osteoporosis is an uncommon cause of hip pain. It affects mostly healthy middle-aged men, and women in the third trimester of pregnancy. The aetiology is unknown. Eight patients (3 females, 5males) who were diagnosed as transient regional osteoporosis of hip were included in the study. Long-term results of all the patients were evaluated. Their mean follow-up duration was 5.1 years. Following every hip involvement, after a mean duration of 6.6 months, all the patients were asymptomatic and returned to full activitiy without residual effects. Both hips were affected in 5 patients, in 4 of which the involvement was migratory. Migratory involvement duration ranged from 3 months to 4 years. In conclusion, Transient regional osteoporosis is self-limiting and resolves symptomatically and radiologically within some months of presentation.